Chemical Composition, Nutrient Adequacy and Organoleptic Qualities of Infant Complementary Food Mixes Made from Combination of Digitaria exilis, Sesamum indicum and Glycine max - Ibeanu, V.; Ene-Obong, H.; Onyechi, U.; Peter-Ogba, G. (Pakistan Journal of Nutrition, 2014)
The best nourishment for infants at birth is breast milk. As from six months of age, the child’s energy and nutrient requirements increase more than breast milk contains. To fill this gap, other foods are introduced to complement breast milk. Foods given to children to augment energy/nutrient content of breast milk are called complementary foods. This study evaluated the chemical composition, nutrient adequacy and organoleptic qualities of complementary food mixes made from Digitaria exilis, Sesamum indicum and Glycine max. Digitaria exilis was fermented and sundried; Sesamum indicum roasted and Glycine max boiled, fermented and sundried before milling separately into flour and subsequently combined at different ratios to produce Digitaria exilis70 and Sesamum indicum30 (D70S30); Digitaria exilis70 and Glyxine max30 (D70G30); Digitaria exilis70 Sesamum indicum15 Glyxine max15 (D70S15G15); Digitaria exilis70 Sesamum indicum20 Glyxine max10 (D70S20G10) and Digitaria exilis70, Glyxine max20 and Sesamum indicum10 (D70G20S10). Formulated flour mixes and gruels produced were chemically and organoleptically assessed, respectively using standard procedures. A commercial product served as control. Means were compared statistically. D70G30 mix had more protein (19.26%), folate (108.71 mg) and lowest zinc (3.24 mg) than others. The mixes had above 400 kcal energy, 11.3 to 13.01 mg iron and 190.28 to 198.34mg calcium. Protein, iron, zinc and folate in most of the mixes met 50-100% RNI for the under-fives. The D70G30, D70S15G15, D70S20G10 and D70G30 had highest colour (6.80), texture (7.90), flavor (6.50) and general acceptability (6.70) ratings, respectively. The D70G30 had the best nutritional and general acceptability attributes for complementary feeding.